2016
DOI: 10.1007/s11095-016-1969-2
|View full text |Cite
|
Sign up to set email alerts
|

Initial Drug Dissolution from Amorphous Solid Dispersions Controlled by Polymer Dissolution and Drug-Polymer Interaction

Abstract: The initial drug release from an ASD was controlled by 1) the polymer release rate; 2) the strength of drug-polymer interaction, including the intrinsic interaction caused by the chemistry of the drug and the polymer (measured by the χ value), as well as that the apparent interaction caused by the drug-polymer ratio (measure by the extent of peak shift on spectroscopic analysis); and 3) the level of mixing homogeneity between the drug and polymer. In summary, the selection of polymer, drug-polymer ratio, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 29 publications
4
70
0
Order By: Relevance
“…In an earlier study, we reported that intrinsic dissolution rate of ASDs was significantly different from that of physical blends, based on the comparisons of ketoconazole (KTZ) ASD systems using PVP, PVPVA, or HPMC-AS as the polymer carriers. 23 We attributed these findings to a nonuniform molecular distribution of drug and polymer in physical mixture and the overall interaction strength. 23 With the presence of homogeneous mixing and specific drugpolymer interaction, drug and polymer dissolved at approximately the same rate from ASDs, whereas a nonhomogeneous mixing state and insufficient drug-polymer interaction resulted in slower drug dissolution rate compared with polymer release rate.…”
Section: The Impact Of Amorphous Phase Separation On the Dissolution mentioning
confidence: 98%
See 3 more Smart Citations
“…In an earlier study, we reported that intrinsic dissolution rate of ASDs was significantly different from that of physical blends, based on the comparisons of ketoconazole (KTZ) ASD systems using PVP, PVPVA, or HPMC-AS as the polymer carriers. 23 We attributed these findings to a nonuniform molecular distribution of drug and polymer in physical mixture and the overall interaction strength. 23 With the presence of homogeneous mixing and specific drugpolymer interaction, drug and polymer dissolved at approximately the same rate from ASDs, whereas a nonhomogeneous mixing state and insufficient drug-polymer interaction resulted in slower drug dissolution rate compared with polymer release rate.…”
Section: The Impact Of Amorphous Phase Separation On the Dissolution mentioning
confidence: 98%
“…23 We attributed these findings to a nonuniform molecular distribution of drug and polymer in physical mixture and the overall interaction strength. 23 With the presence of homogeneous mixing and specific drugpolymer interaction, drug and polymer dissolved at approximately the same rate from ASDs, whereas a nonhomogeneous mixing state and insufficient drug-polymer interaction resulted in slower drug dissolution rate compared with polymer release rate. 23 However, in the current BMS-817399/PVP-40/60 ASD, polymer release rate was about 3 times of the drug release rate (0.77 vs. 0.21 mg/cm 2 /min).…”
Section: The Impact Of Amorphous Phase Separation On the Dissolution mentioning
confidence: 98%
See 2 more Smart Citations
“…In the literature, also the impact of drug-polymer interactions on the dissolution performance was investigated. A study by Chen et al (2016a) investigated the formulation factors that control drug and polymer dissolution rates by an example of ketoconazole ASDs of different polymers. Authors distinguished the systems' behavior according to the drugpolymer interaction, represented by Flory-Huggins interaction parameter.…”
Section: Effects Of Drug-polymer Interactionsmentioning
confidence: 99%